ANALISIS DAYA SAING EKSPOR KOPI INDONESIA DENGAN BRAZIL DI PASAR INTERNASIONAL - Santoso, Khairana Maheswari (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
One of the largest coffee-producing countries in the world is Indonesia. Indonesia is in fourth place as the largest producer of the coffee commodities after Brazil, Vietnam, and Cambodia. The area of Indonesian coffee plantations reached 24,487.19 ha in 2020 (according to the status of exploitation (000 Ha). With extensive plantations and abundant yields, it provides an advantage for Indonesia to export its coffee products. The coffee commodity is one that contributes a large amount of foreign exchange to the Indonesian economy. Good and quality coffee results make many countries choose to import coffee to Indonesia, the destination countries for Indonesia's highest coffee exports include the United States of America, Egypt, Japan, and Spain. Even so, Indonesia still has competitors from producing countries the largest coffee such as Brazil which is the largest coffee-producing country in the world according to the International Coffee Organization so Indonesia must have strong competitiveness to be able to compete and excel from competing countries. This research is intended to determine the value of the export competitiveness of coffee commodities owned by Indonesia with competing countries, namely Brazil da in facing competition in the international market. This study applies a quantitative descriptive method and a Revealed Comparative Advantage (RCA) calculation method and uses secondary data and time series from BPS, Trade Map and other official websites. Keyword : Coffee, export, competitiveness, time series, RCA